Distance Inputs and the Space-Economy 1 Part I: The Conceptual Framework - Isard, Walter (Quarterly Journal of Economics, 1951)
I. Empirical regularities and the distance factor, 181. — II. The need for and definition of distance inputs, 186. — III. Distance inputs contrasted with capital inputs: spatial roundaboutness and extent of production; space preference and discounting, 190. — IV. Transport rate: the price of a distance input, 195. — V. Distance inputs and the classification of factors, 197.